Features of the pharmaceutical market of the Republic of Uzbekistan - Musayeva Shoira Azimovna; Marufov Zokir Abdurozikovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article focuses on the protection of public health in our country, providing our compatriots with cheap and high-quality medicines, modern medical equipment, rules for the organization of production of medicines and medical devices and their quality control.